2010
DOI: 10.1128/jvi.01075-10
|View full text |Cite
|
Sign up to set email alerts
|

The F Gene of the Osaka-2 Strain of Measles Virus Derived from a Case of Subacute Sclerosing Panencephalitis Is a Major Determinant of Neurovirulence

Abstract: Measles virus (MV) is the causative agent for acute measles and subacute sclerosing panencephalitis (SSPE). Although numerous mutations have been found in the MV genome of SSPE strains, the mutations responsible for the neurovirulence have not been determined. We previously reported that the SSPE Osaka-2 strain but not the wild-type strains of MV induced acute encephalopathy when they were inoculated intracerebrally into 3-week-old hamsters. The recombinant MV system was adapted for the current study to identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 72 publications
(77 reference statements)
2
51
0
Order By: Relevance
“…In the present study, we used 10-day-old suckling hamsters, as 3-week-old weanling hamsters were not susceptible to the viruses, unlike the prior report using virus-like particles (54). This suggests that the maturity of the host immune system is also important for MV neuropathogenicity in hamsters.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…In the present study, we used 10-day-old suckling hamsters, as 3-week-old weanling hamsters were not susceptible to the viruses, unlike the prior report using virus-like particles (54). This suggests that the maturity of the host immune system is also important for MV neuropathogenicity in hamsters.…”
Section: Discussionmentioning
confidence: 75%
“…2). Using virus-like particles, Ayata et al have reported that the neurovirulence of one SSPE strain (Osaka-2) is related to the ability of its F protein to induce syncytia in Vero cells, which is attributed to a single substitution (T461I) (54).…”
Section: Substitutions In the F Protein That Enhance Its Fusion Activmentioning
confidence: 99%
“…MV generally does not induce neurological disease in experimental small animals such as hamsters and ferrets, whereas the SSPE virus induces lethal neurological diseases in these animal models (1,37). However, the mutations responsible for the neurovirulence of the SSPE virus have not been identified.…”
Section: Discussionmentioning
confidence: 99%
“…Ayata et al reported that a recombinant virus containing the F gene of the SSPE Osaka-2 strain alone induced lethal encephalopathy in a hamster model. Furthermore, a single T461I substitution in the F protein transformed the nonneuropathogenic wild-type MV into a lethal virus (37). However, it is unknown whether the F-gene mutation is common among all SSPE virus strains.…”
Section: Discussionmentioning
confidence: 99%
“…Some SSPE strains have mutations in the F gene that variously result in an elongated or a shortened cytoplasmic domain (Billeter et al, 1994;Ning et al, 2002). A single amino acid substitution in the F protein transformed the non neuropathogenic wild-type MV IC323 strain into a lethal virus similar to the SSPE Osaka-2 strain in hamsters (Ayata et al, 2010). The demyelination observed in SSPE could be the result of several mechanisms.…”
Section: Molecular Basis Of Cns Diseasementioning
confidence: 99%